PENYULUHAN PENGELOLAAN GIZI PADA SAAT KEHAMILAN UNTUK MENCEGAH STUNTING PADA ANAK DI PUSKESMAS SIJUNJUNG - Siska Ferilda; Elsa Marsellin; Muhammad Rizki Saputra; Betty Fitriyasti; Sri Wahyuni; Fidiariani Sjaaf (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Stunting or chronic malnutrition is another form of growth failure and chronic malnutrition. This situation has been going on for a long time, not like acute malnutrition. Stunting can also occur before birth and is caused by very inadequate nutritional intake during pregnancy, very poor parenting patterns, low quality of food in line with the frequency of infections so that it can inhibit growth. The service was carried out using the lecture method in which groups of pregnant women at the Lubuk Tarok Health Center were given counseling on nutrition management during pregnancy to prevent stunting in children and then discussions were held. Before and after counseling, questionnaires were distributed to assess the level of success of the counseling carried out